2008
DOI: 10.4315/0362-028x-71.1.134
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ground Beef–Derived Fatty Acid Inhibitors of Autoinducer-2–Based Cell Signaling

Abstract: Autoinducer-2 (AI-2) molecules are used by several microorganisms to modulate various processes, including bioluminescence, biofilm formation, and virulence expression. Certain food matrices, including ground beef extracts, possess compounds capable of inhibiting AI-2 activity. In the present study, we identified and characterized these AI-2 inhibitors from ground beef extract using hexane solvent extraction and gas chromatography. Gas chromatographic analysis revealed the presence of several fatty acids such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 28 publications
(32 reference statements)
2
23
0
1
Order By: Relevance
“…This is the case with the findings of Soni et al (116,117) who reported that the presence of AI-2 molecules promoted the survival of E. coli O157:H7 cells, whereas the protective effect of AI-2 molecules was negated in the presence of ground beef extracts that contained a significant amount of inhibitory activity.…”
Section: Quorum Sensing In the Context Of Food And Food Processingsupporting
confidence: 76%
See 2 more Smart Citations
“…This is the case with the findings of Soni et al (116,117) who reported that the presence of AI-2 molecules promoted the survival of E. coli O157:H7 cells, whereas the protective effect of AI-2 molecules was negated in the presence of ground beef extracts that contained a significant amount of inhibitory activity.…”
Section: Quorum Sensing In the Context Of Food And Food Processingsupporting
confidence: 76%
“…So far, few studies have investigated the influence of food system conditions on autoinducer signal production by foodborne pathogens (9,17,70,79,80) and the influence of these QS signals on the survival/growth of pathogenic bacteria in foods (9,115). Soni et al (116,117), for example, reported that the survival and virulence expression of a luxS mutant strain of Escherichia coli O157:H7 was enhanced in the presence of autoinducer-2 (AI-2). Similarly, production of AI-2 by Salmonella enterica serovar Typhimurium contributed significantly to its ability to colonize in chicken intestine compared to the LuxS Ϫ mutant strain (9).…”
Section: Bacterial Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these examples, a series of AHL analogues with varying side chain lengths and substitutions have been synthesized de novo and are highly effective in inhibiting the QS systems of several Gram-negative bacteria (30,(40)(41)(42)(43)(44). The few known ex-amples of interference with AI-2 often represent more indirect mechanisms, such as inhibition of AI-2 synthesis or phosphorylation processes involved in interspecies signal processes (9,14,45,46). However, several synthetic AI-2 analogues have been shown to compete with natural AI-2 for binding to the corresponding receptor (47)(48)(49)(50).…”
Section: Q Uorum Sensing (Qs) Is the Cell-cell Communication Betweenmentioning
confidence: 99%
“…Usually low polarity DB-1 or DB-5 columns, and equivalent columns, are employed for these chromatographic separations. Even when detection of signaling molecules has been reported by FID detectors (Soni et al, 2008) and electron capture detectors (ECD), the most used detector is the single quadrupole MS detector, in both positive and negative detection modes. In addition, for increase the sensibility of the methods for previously identified signaling molecules, selected ion monitoring (SIM) detection modes are preferred over the full SCAN detection mode.…”
Section: Extraction Structural and Stereochemical Analysis By Gc Of mentioning
confidence: 99%